A study of lipid profile in subclinical hypothyroidism in tertiary care hospital, Kolkata, India - Saha, Kaushik; Saha, Dipa (International Journal of Advances in Medicine, 2020)
Background: Objective was to study lipid profile in patients of subclinical hypothyroidism in tertiary centre in Kolkata, West Bengal and compare the same with matched controls. Methods: This observational study (single exposure) was conducted May 2019 to Nov 2019 at Department of Medicine, KPC Medical College, Jadavpur, Kolkata in subjects diagnosed with Sub Clinical Hypothyroidism [defined as normal T3 or FT3, normal T4 or FT4, and with increased TSH. Sixty patients with subclinical hypothyroidism were selected after careful exclusion; lipid profile was compared with matched controls. Results: Between the two groups (group I - controls vs. group II - cases), the values were as follows: Mean serum total T3 value was 114.03±29.22 ng/dl vs. 106.15±36.24 ng/dl (p = 0.3476); mean total T4 was 7.07±1.69 μg/dl vs. 6.86±1.31 μg/dl (p = 0.535); mean TSH was 3.17±1.28 μIU/ml vs. 9.77±4.19 μIU/ml (p <0.0001). Lipid profile pattern (group I vs. group II) was as follows: Mean total cholesterol (TC) 125.50±9.18 mg/dl vs. 162.07±42.32 mg/dl (p <0.0001), mean triglycerides (TG) is 136.65±14.82 mg/dl vs. 148.90±65.27 mg/dl (p = 0.3236), low-density lipoprotein (LDL)-cholesterol is 62.17±7.40 mg/dl vs. 98.81±33.26 mg/dl (p <0.0001), high-density lipoprotein (HDL)-cholesterol 39.17±6.62 mg/dl vs. 34.27±9.63 mg/dl (p = 0.0702), very low-density lipoprotein (VLDL) levels are 34.54±15.38 mg/dl vs. 32.08±13.21 mg/dl (p = 0.5245).. Conclusions: Subclinical hypothyroidism is associated with increased serum total cholesterol and LDL-Cholesterol levels. Therefore, there is a potential association between Subclinical hypothyroidism and atherosclerosis.